Peran Kepala Sekolah dalam Menumbuhkan Kepedulian Lingkungan di Sekolah (Studi Kasus di SMP Negeri 5 Jombang) - Supriyadi; Suwandi (Menara Tebuireng, 2019)
Caring for the environment can create good conditions for schools to become a comfortable place of learning and awareness of the school community, so that in the future these school members can take responsibility for efforts to save the environment for Indonesia. The focus of this research and development includes: 1) The role of school principals in fostering awareness in SMPN 5 Jombang, 2) Knowing the characteristics of environmental care in SMPN 5 Jombang, 3) Knowing the constraints and solutions for environmental care in SMPN 5 Jombang. The research uses descriptive qualitative research with a phenomenological approach. Data collection techniques using observation, interviews, and documentation. For data analysis techniques using: data reduction, data display, data verification. To check the validity of the data by: (1) credibility: a. extension of participation, b. perseverance of observation, c. triangulation, d. Negative Case Analysis, e. Using reference material, f. using member check, (2) transferability, (3) dependability, (4) confirmability. The results showed that: (1) Principal leadership is very important because it is a driving force for school resources, especially teachers and school employees, (2) characteristics in the form of environmental care activities that can make the character of students who care about the environment, (3) obstacles and solutions in growing environmental care, namely: In schools there are students who have not complied with adiwiyata school regulations, new students who are not familiar with environmental culture due to differences in family background, narrow land, and the solution is that school residents must work together same to remind teachers especially to students, policing through environmental regulations in the form of prohibitions and penalties